The Strategic Perils of Delayed Differentiation - Anand, Krishnan S.; Girotra, Karan (Management Science, 2007)
The value of delayed differentiation (also known as postponement) for a monopolist has been extensively studied in the operations literature. We analyze the case of (imperfectly) competitive markets with demand uncertainty, wherein the choice of supply chain configuration (i.e., early or delayed differentiation) is endogenous to the competing firms. We characterize firms’ choices in equilibrium and analyze the effects of these choices on quantities sold, profits, consumer surplus, and welfare. We demonstrate that purely strategic considerations not previously identified in the literature play a pivotal role in determining the value of delayed differentiation. In the face of either entry threats or competition, these strategic effects can significantly diminish the value of delayed differentiation. In fact, under plausible conditions, these effects dominate the traditional risk-pooling benefits associated with delayed differentiation, in which case early differentiation is the dominant strategy for firms, even under cost parity with delayed differentiation. We extend the main model to study the effects of alternate market structures, asymmetric markets, and inventory holdback. Our results—in particular that for a broad range of parameter values, early differentiation is a dominant strategy even under cost parity with delayed differentiation—are robust to these relaxations.